Grip and Pinch Strength Norms for Michigan Workers - Joel M. Phillips M.S., OTRL; Debra K . Lindstrom-Hazel Ph.D., OTRL; Samantha Harrow Swantek M.S., OTRL; Erin Courtnay Catalano M.S., OTRL (Scholarworks @ WMU, 2013)
The purpose of this study was to create a norm reference of current grip and pinch strength norms for working-age Michigan adults. This normative study included a convenience sample of 179 volunteers who were employees at car plants in South East Michigan or hospital sites in West Michigan. Participants' ages ranged from between 20 and 62 years of age with a mean age of 49.15 years. There were 78 females (44%) and 101 males (56%). Subjects were classified by gender and in the age categories of ages 20 to 49 years and ages 50-62 years. Grip and pinch strength norms were collected following the American Society of Hand Therapy protocol. The norms from these working adults were calculated with descriptive statistics for males and females in two age classifications: ages 20 to 49 and ages 50 to 62 years. Standard Errors (SE) are better than the 1985 norms for both males and females ages 20 to 49 years. SEs are higher than the ages 20 to 49 years' norms for the ages 50 to 62 years age categories in both males and females. These norms offer a point of comparison for clinicians to use for clients in Michigan who are ages 20 to 62 years and who have a goal to improve their grip strength. Clients' grip and pinch strength could be compared to their age level or gender norms using the comparison for one standard deviation above, below, or at the means.